BLAMING THE VICTIM : REPRESENTASI PEREMPUAN KORBAN PEMERKOSAAN DI MEDIA MASSA (Analisis Semiotika dalam Pemberitaan di Koran Suara Merdeka Desember 2011 – Februari 2012) - Putri, Dani Marsa Aria (Interaksi, 2012)
Mass media especially newspaper is one of the medium that used to convey themessages which the readers will processed that messages as the reality through the procesof interpretation. News about rape in Suara Merdeka give us the image of women as rapevictim. How the women potrayed in the news will gives society the idea of women asrape victim. It also affect how society seeing them as victim. The purpose of this study is to see how Suara Merdeka represent women as rapevictims in their daily news which made by the journalists. Theory that used in this studyis the Muted Group Theory by Cheris Kramarae. Reseacher will try to find the meaningsthat showns in news through semiotics with syntagmatic and paradigm analysis.Syntagmatic see meanings that seen through text, meanwhile paradigm looks beyond intothe meaning of text. In paradigm analysis, we used five major codes by Roland Barthes. The results of this study indicate that basically, in the news that Suara Merdekawrites about rape represent women as rape victims as passive figure, weak, and helplesswhen it comes to facing the perpetrators in every case of rape. Women are seen assomeone who blamed when rape happens. They considered as the cause of rape for theirpresence. Women as rape victim also surrounded by the values in the society that makesthem feel disanvantaged. Few stigma and labels that given by society when they becomerape victims can give them a certain psychological burden.